APPLICATION OF CALORIMETRY CONCEPTS IN BROILERS PRODUCTION - RESTELATTO, RASIEL; MENDES, ANGÉLICA S.; POSSENTI, MARCO A.; PAIXÃO, SANDRO J. (Revista Brasileira de Engenharia de Biossistemas, 2008)
Methods of packing heat for broilers are analyzed and studied frequently. The results of theseresearches are such that the poultry activity in Brazil to develop and grow fast. Many discussionsare raised and discussed, but the desired result is to enable the farmers a balanced view betweenthe various experiments and options available, to get the maximum yield with the final product. Toobtain a good return with the poultry activity and planned facilities are needed, enabling the controlof temperature within the standards required by species, with a capacity of adjustments betweenthe four seasons. Thus, this paper aims to highlight through the scientific literature referenced, therelevance of this issue and the correlaction the concepts of calorimetry in the final result of apoultry activity in which they want the most productive potential of the species.